Method for producing a charge transport layer and light emitting diode
Patent Information
- Application Number
- CN202011552242.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2040-12-24
AI Technical Summary
[0006]本发明的一个目的在于克服现有技术的上述不足,提供一种电荷传输层的制备方法和发光二极管,以解决现有胶体金属氧化物纳米晶体形成电荷传输层存在局部缺陷而使得激子迁移率低或解离现象的技术问题
[0014]本发明电荷传输层的制备方法将第二溶液和第一溶液在分别形成膜层或者先形成混合物后再成膜后,这样,功能性材料会与金属氧化物纳米材料表面的金属阳离子悬挂键结合,达到封端的效果,当电荷传输湿膜层中溶剂在挥发的过程中,表面结合有功能性材料的金属氧化物纳米材料会先形成一种类似与“寡聚体”的稳定状态,并在沉积过程中这些“寡聚体”会发生类似于高分子聚合的有序排列,使金属氧化物纳米材料在沉积过程中变得有序,减少成膜过程产生缺陷的机会,这样,制备的电荷传输层中金属氧化物纳米材料能够有序排列,电荷传输层缺陷少或者不存在缺陷,从而使得电荷传输层对激子迁移速率高,且能够避免激子发生解离的现象。另外,电荷传输层制备方法形成层结构条件可控,有效保证了制备电荷传输层性能的稳定,而且效率高。
Smart Images

Figure CN114678487B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optoelectronic technology, and particularly relates to a method for preparing a charge transport layer and a light-emitting diode. Background Technology
[0002] For state-of-the-art solution-processed optoelectronic devices, the charge transport layer (CTL), also known as the electron transport layer (ETL) and hole transport layer (HTL), is an essential component. The CTL not only affects charge injection within the active layer but also influences many other fundamental physical processes in device operation, such as interfacial charge recombination and light extraction (or light absorption) in LEDs (or solar cells).
[0003] In recent years, colloidal metal oxide nanocrystals have attracted considerable interest as colloidal thermal liquid crystals (CTLs). The best example is an electrochemical liquid crystal (ETL) based on colloidal ZnO nanocrystals, which has been used in several high-performing prototype devices. Furthermore, colloidal oxide nanocrystals are fully compatible with large-scale industrial production, thus showing promising prospects for high-performance, low-cost, and large-area devices.
[0004] Current research on the application of colloidal metal oxide nanocrystals in optoelectronic devices mainly focuses on the synthesis chemistry of colloidal oxide nanocrystals, the ligand chemistry that may be applicable to colloidal oxide nanocrystals, and the chemistry related to post-deposition processing. Regarding post-deposition processing, current ink solutions employ orthogonal solvent systems to deposit adjacent functional layers. Furthermore, by adjusting the ink's viscosity and surface tension, continuous, pinhole-free, and overall thickness-controllable CTL films can be achieved.
[0005] However, in practical applications, it has been found that the CTL films deposited in the current manner still have certain shortcomings. For example, the defects caused by the local aggregation of colloidal metal oxide nanocrystals in the film not only reduce the exciton mobility of the CTL, but also the excitons that have already formed may dissociate at the defect sites, leading to a decrease in device efficiency. A major reason for local defects is the uncontrolled deposition process, and there are currently few reports on research into local defects in CTL films. Summary of the Invention
[0006] One objective of this invention is to overcome the aforementioned deficiencies of the prior art and provide a method for preparing a charge transport layer and a light-emitting diode, so as to solve the technical problem that the existing colloidal metal oxide nanocrystals have local defects in the formation of charge transport layers, resulting in low exciton mobility or dissociation.
[0007] To achieve the above-mentioned objective, one aspect of the present invention provides a method for fabricating a charge transport layer. The method for fabricating the charge transport layer includes the following steps:
[0008] A first film layer is formed using a first solution containing a functional material, and a second film layer is formed using a second solution containing a charge transport material, wherein the first film layer and the second film layer are adjacent to each other, or a mixed film layer is formed using a mixed solution of the first solution and the second solution;
[0009] The functional material is removed to obtain the charge transport layer;
[0010] The functional material is an organic compound containing electron-donating groups, and the surface of the charge transport material has metal cation dangling bonds, wherein the electron-donating groups can bind to the metal cation dangling bonds.
[0011] In another aspect, the present invention provides a light-emitting diode (LED). The LED includes an electron transport layer and / or a hole transport layer, wherein the electron transport layer is formed according to the method for preparing a charge transport layer of the present invention, and wherein the charge transport material is an electron transport material.
[0012] The hole transport layer is prepared according to the method for preparing the charge transport layer of the present invention, wherein the charge transport material is a hole transport material.
[0013] Compared with the prior art, the present invention has the following technical effects:
[0014] The method for preparing the charge transport layer of this invention involves forming films from a second solution and a first solution separately, or first forming a mixture and then forming a film. This allows the functional material to bind to the dangling bonds of metal cations on the surface of the metal oxide nanomaterials, achieving a capping effect. During the evaporation of the solvent in the charge transport wet film, the metal oxide nanomaterials with the functional material bound to their surface first form a stable state similar to "oligomers." During deposition, these "oligomers" undergo an ordered arrangement similar to polymer polymerization, making the metal oxide nanomaterials more ordered during deposition and reducing the chance of defects during film formation. Thus, the prepared charge transport layer has an ordered arrangement of metal oxide nanomaterials, with few or no defects, resulting in a high exciton migration rate and preventing exciton dissociation. Furthermore, the charge transport layer preparation method allows for controllable layer structure conditions, effectively ensuring the stability of the prepared charge transport layer's performance and high efficiency.
[0015] The light-emitting diode of the present invention contains a charge transport layer prepared by the above-described method for preparing the charge transport layer of the present invention, and an electron transport layer and / or a hole transport layer prepared by the above-described method for preparing the charge transport layer of the present invention. In this way, the metal oxide nanomaterials contained in the electron transport layer and / or hole transport layer of the light-emitting diode can be arranged in an orderly manner, and the charge transport layer has small or no defects, thereby endowing the charge transport layer with the characteristic of high exciton migration rate, and thus endowing the light-emitting diode of the present invention with high luminous efficiency. Attached Figure Description
[0016] Figure 1 Figure 1 is a schematic diagram of the process flow for preparing the charge transport layer according to an embodiment of the present invention; wherein, Figure 2a is a first method for preparing the charge transport layer according to an embodiment of the present invention, Figure 3b is a second method for preparing the charge transport layer according to an embodiment of the present invention, and Figure 4c is a third method for preparing the charge transport layer according to an embodiment of the present invention.
[0017] Figure 2 This is a schematic diagram of a positive configuration light-emitting diode structure provided in an embodiment of the present invention;
[0018] Figure 3 This is a schematic diagram of a light-emitting diode structure with an inverted configuration provided in an embodiment of the present invention;
[0019] Figure 4 These are EL morphology diagrams of the positive light-emitting diodes provided in Embodiments 1 to 2 and Comparative Example 3 of the present invention; wherein, Figure 4 (a) An EL topography diagram of the positive light-emitting diode provided in Example 1; Figure 4 (b) is an EL topography diagram of the positive light-emitting diode provided in Example 2; Figure 4 (c) is the EL topography of the positive light-emitting diode provided in Comparative Example 3. Detailed Implementation
[0020] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0021] On one hand, embodiments of the present invention provide a method for preparing a charge transport layer. The method includes forming a first film layer using a first solution containing a functional material and forming a second film layer using a second solution containing a charge transport material, such that the first and second film layers are adjacent to each other, and then removing the functional material to obtain the charge transport layer; or forming a mixed film layer using a mixture of the first and second solutions, and then removing the functional material to obtain the charge transport layer. Therefore, in these embodiments, the method for preparing a charge transport layer includes at least the following three methods:
[0022] The first method for preparing the charge transport layer:
[0023] The process flow of the first preparation method is as follows: Figure 1 As shown in (a), the steps include:
[0024] S01: A second film layer 2 is formed on a substrate 1 using a second solution containing a charge transport material;
[0025] S02: A first film layer 3 is formed on the surface of the second film layer 2 using a first solution containing functional materials;
[0026] S03: Remove the functional materials contained in the composite wet film layer formed by the second film layer 2 and the first film layer 3 to form a charge transport layer.
[0027] The process flow for the second preparation method is as follows: Figure 1 As shown in (b), the steps include:
[0028] S04: A first film layer 3 is formed on a substrate 1 using a first solution containing a functional material;
[0029] S05: A first film layer 2 is formed on the first film layer 3 using a second solution containing a charge transport material;
[0030] S06: Remove the functional materials contained in the composite wet film layer formed by the second film layer 2 and the first film layer 3 to form a charge transport layer.
[0031] The process flow of the third preparation method is as follows: Figure 1 As shown in (c), it includes the following steps:
[0032] S07: A mixed film layer 4 is formed on a substrate 1 by mixing a first solution containing a functional material and a second solution containing a charge transport material;
[0033] S08: Remove the functional materials contained in the mixed film layer 4 to form a charge transport layer.
[0034] In the above-mentioned method for preparing the charge transport layer, the functional material contained in the first solution in steps S02, S04, and S07 is an organic compound containing electron-donating groups. The surface of the charge transport material contained in the second solution in steps S01, S05, and S07 has metal cation dangling bonds, and the electron-donating groups in the functional material can bind to the metal cation dangling bonds on the surface of the charge transport material. Thus, when the first solution containing the functional material and the second solution containing the charge transport material are used to form the first film layer 3 and the second film layer 2 in steps S01 to S02 and steps S04 to S05, respectively, since these are wet film layers, the solvents of the two layers will fuse. At this time, the functional material will directly contact the charge transport material in the composite wet film layer, thereby allowing the electron-donating groups in the functional material to bind to the metal cation dangling bonds on the surface of the charge transport material. In the mixed solution in step S07, the functional material and the charge transport material are directly contacted in the mixed film layer 4. Thus, the electron-donating groups in the functional material bind to the metal cation dangling bonds on the surface of the charge transport material, achieving a sealing effect. During the removal of the contained functional materials in steps S03, S06, and S08, the solvent in the composite wet film layer or mixed film layer 4 evaporates, causing the charge transport material with the functional material bonded to its surface to first form a stable state similar to an "oligomer." During deposition, these "oligomers" undergo an ordered arrangement similar to polymer polymerization, making the charge transport material more ordered during deposition and reducing the chance of defects in the film formation process. Therefore, by incorporating functional materials in the corresponding process steps, this embodiment of the invention enables the charge transport material in the prepared charge transport layer to be arranged in an orderly manner, resulting in fewer or no defects in the charge transport layer. This gives the charge transport layer a high exciton migration rate and avoids exciton dissociation.
[0035] Through research on functional materials, the inventors have found that the functional materials suitable for embodiments of the present invention preferably meet the following three characteristics: 1) solution-processable; 2) possessing electron-donating groups, capable of forming "oligomers" with charge-transporting materials to achieve the desired effect; and 3) easily removable. Among these, characteristics 1) and 2) are considered fundamental requirements, while characteristic 3) is a preferred characteristic. Therefore, in one embodiment, the aforementioned functional material includes triethylamine.
[0036] Based on the aforementioned functions and preferred types of functional materials, in one embodiment, the volume ratio of functional material to solvent in the first solution during steps S02, S04, and S07 is 1:(1-50). In another embodiment, the solvent in the first solution includes at least one of acetone, n-butanol, tetrahydrofuran, and methyl formate. By controlling and optimizing the concentration of functional materials in the first solution and optimizing the selection of solvents, the film-forming uniformity of the first film layer 3 or the mixed film layer 4 is improved, thereby enabling the functional materials and charge transport materials to fully function, thereby improving the orderly arrangement of the charge transport materials in the formed charge transport layer, resulting in fewer or no defects in the charge transport layer.
[0037] In another embodiment, by controlling the thickness of the first film layer 3 in steps S02 and S04, or the mixing ratio of the functional material and charge transport material in the mixed solution in step S07, the functional material is made in sufficient quantity relative to the charge transport material. This allows the functional material to achieve a capping effect by bonding the metal cation dangling bonds on the surface of the charge transport material, and ensures that the charge transport material is fully and orderly arranged in the formed charge transport layer. This further reduces or completely eliminates defects in the charge transport layer, thereby further optimizing the exciton transport efficiency of the charge transport layer. Therefore, in one embodiment, the molar ratio of the functional material in the first film layer 3 to the charge transport material in the second film layer 2 is 1.5 to 3:1. Alternatively, in the mixed solution of step S07, i.e., the mixed film layer 4, the molar ratio of the functional material to the charge transport material is 1.5 to 3:1.
[0038] In addition, the method for forming the first film layer 3 in steps S02 and S04 can be the same as the existing solution film forming method. Specifically, the first film layer 3 can be formed by referring to the charge transport layer film forming method. For example, in a specific embodiment, the method for forming the first film layer 3 includes spin coating, inkjet printing, spraying, doctor blade coating and other methods.
[0039] In steps S01, S05, and S07, the second solution can be a commonly used second solution for preparing a charge transport layer. Naturally, the second solution contains a charge transport material. In this embodiment of the invention, the charge transport material includes metal oxide nanomaterials (metal oxide nanocrystal materials), meaning that the second solution in steps S01, S05, and S07 contains metal oxide nanomaterials.
[0040] Since electric charge includes electrons and holes, the second solution in steps S01, S05, and S07 can be either an electron transport material ink or a hole transport material ink. When the second solution in steps S01, S05, and S07 is an electron transport material ink, the electron transport material contained in the electron transport material ink includes metal oxide nanomaterials, and the metal oxide nanomaterials are nano-metal oxide electron transport materials. In one embodiment, the nano-metal oxide electron transport material includes at least one of ZnO, SnO, TiO2, and ZrO2, or includes at least one of ZnO, SnO, TiO2, and ZrO2 doped with a metal; wherein the doping metal used to dope at least one of ZnO, SnO, TiO2, and ZrO2 includes at least one of Li, Al, Mg, Cs, In, Ga, and Zr. The selection of this nano-metal oxide electron transport material not only enables the formed electron transport layer to have good continuity, no pinholes, and overall thickness, as well as high electron transport efficiency, but more importantly, it can interact with the functional materials contained in the first solution in steps S02, S04, and S07 as described above, thereby improving the electron transport layer to have fewer or no defects and high electron transport efficiency.
[0041] When the second solution in steps S01, S05, and S07 is a hole transport material ink, the hole transport material contained in the hole transport material ink includes metal oxide nanomaterials, and the metal oxide nanomaterials are nano-metal oxide hole transport materials. In one embodiment, the nano-metal oxide hole transport material includes at least one of MoO3, NiO, V2O5, and WO3, or includes at least one of MoO3, NiO, V2O5, and WO3 doped with a metal; wherein the doping metal used to dope at least one of MoO3, NiO, V2O5, and WO3 includes at least one of Li, Al, Mg, Cs, In, Ga, and Zr.
[0042] Furthermore, the concentration of the second solution in steps S01, S05, and S07 can be adjusted according to the requirements of the method for forming the charge transport wet film layer, such as the second film layer 2 and the mixed film layer 4. To ensure that the second film layer 2 and the first film layer 3 can fully fuse to improve the quality of the composite wet film layer, if the charge transport layer is prepared according to the first or second preparation method described above, after forming the second film layer 2 in step S01, step S02 (i.e., forming the first film layer 3) should be performed immediately; or after forming the first film layer 3 in step S04, step S05 (i.e., forming the second film layer 2) should be performed immediately, allowing sufficient time for the second film layer 2 and the first film layer 3 to fuse.
[0043] Furthermore, the methods for forming the second film layer 2 in steps S01 and S05 and the mixed film layer 4 in step S07 can be based on existing solution film-forming methods. For example, in specific embodiments, the methods for forming the second film layer 2 and the mixed film layer 4 include spin coating, inkjet printing, spraying, and blade coating. When spin coating is used to form the second film layer 2, the solvents of the second film layer 2 and the first film layer 3 are miscible and have similar polarities. Due to the characteristics of the spin coating process, a small amount of the second film layer 3 may be peeled off. This can be compensated for by prior statistical analysis and calculation of the loss amount and by adjusting the thickness of the second film layer 2.
[0044] Secondly, the substrate 1 in steps S01, S04, and S07 can be any substrate on which a charge transport layer needs to be formed on the surface of the corresponding component or device. Based on the conventional applications of charge transport layers, the substrate is preferably the surface of the corresponding component contained in an electroluminescent device (such as a light-emitting diode), such as the positive electrode, negative electrode, electron injection layer, hole injection layer, or light-emitting layer, depending on the specific order in which the corresponding electroluminescent device is fabricated.
[0045] The methods for removing functional materials to obtain the charge transport layer in the above embodiments, such as steps S03, S06, and S08, include drying the first film layer 3 and the second film layer 2 or the mixed film layer 4 to effectively remove the functional materials from the composite wet film layer or the mixed film layer 4 while removing the solvent to form the charge transport layer. In one embodiment, the drying method includes the following steps:
[0046] In an inert gas atmosphere, the composite wet film layer or the mixed film layer 4 is heat-treated at 90℃~150℃.
[0047] This drying process causes the solvent and functional materials in the composite wet film layer or mixed film layer 4 to evaporate, solidifying to form a charge transport layer. Furthermore, the drying process, such as a heat treatment time of 90℃ to 150℃, should be sufficient, specifically 5 minutes to 24 hours. The specific time can be adjusted according to the thickness of the composite wet film layer or mixed film layer 4 and the characteristics of the solvent.
[0048] Therefore, the method for preparing the charge transport layer in this embodiment of the invention not only enables the functional material contained in the first solution to interact with the charge transport material in the second solution, allowing the charge transport material to be arranged in an orderly manner in the prepared charge transport layer, resulting in fewer or no defects in the charge transport layer, thus giving the charge transport layer a high exciton migration rate and preventing exciton dissociation. Furthermore, the method for preparing the charge transport layer allows for controllable layer structure conditions, effectively ensuring the stability of the prepared charge transport layer's performance, and is also highly efficient.
[0049] On the other hand, based on the above-described method for preparing the charge transport layer, this embodiment of the invention also provides a light-emitting diode (LED). The LED contains an electron transport layer and a hole transport layer, and of course, it also contains other necessary layer structures, such as a light-emitting layer, an anode, and a cathode. The electron transport layer in the LED is prepared according to the above-described method for preparing the charge transport layer. Therefore, it is natural that the charge transport material contained in the second solution used in preparing the electron transport layer according to the above-described method is an electron transport material.
[0050] Alternatively, the hole transport layer in the light-emitting diode may be a hole transport layer prepared according to the method described above for preparing the charge transport layer. Therefore, it is natural that the charge transport material contained in the second solution used in preparing the hole transport layer according to the method described above is a hole transport material.
[0051] Furthermore, the electron transport layer and hole transport layer in the light-emitting diode can be simultaneously and separately fabricated according to the method for fabricating the charge transport layer described above. Alternatively, either the electron transport layer or the hole transport layer can be fabricated using the same method. In this embodiment of the invention, it is preferable that both the electron transport layer and the hole transport layer are fabricated using the same method for fabricating the charge transport layer described above. This simultaneously improves both electron transport efficiency and hole transport efficiency, thereby increasing the exciton content in the light-emitting layer and thus improving the luminous efficiency of the light-emitting diode, such as increasing the external quantum efficiency (EQE).
[0052] Secondly, depending on the light-emitting material contained in the light-emitting layer, the light-emitting diode in this embodiment of the invention can be a quantum dot light-emitting diode (QLED) or an organic light-emitting diode (OLED). Depending on the structural configuration of the light-emitting diode, the light-emitting diode in this embodiment of the invention can be a positive-type light-emitting diode or an inverted-type light-emitting diode.
[0053] In one embodiment, the structure of a positive light-emitting diode is as follows: Figure 2 As shown, it includes a stacked structure of an anode 10 and a cathode 50 disposed opposite to each other. The anode 10 can be stacked and bonded on a substrate 01, and a light-emitting functional layer is stacked and bonded between the anode 10 and the cathode 50. The light-emitting functional layer includes a light-emitting layer 30, a hole transport layer 20, and an electron transport layer 40. From the anode 10 to the cathode 50, the hole transport layer 20, the light-emitting functional layer 30, and the electron transport layer 40 are stacked sequentially. Furthermore, a hole injection layer can also be disposed between the hole transport layer 20 and the anode 10. Figure 2 (Not shown), an electron injection layer can also be provided between the electron transport layer 40 and the cathode 50. Figure 2 (Not displayed).
[0054] When the hole transport layer 20 is prepared using the method described above for preparing the charge transport layer, the anode 10 is used as the substrate 1, and hole transport material ink is used as the second solution on the outer surface of the anode 10, and the hole transport layer 20 is prepared according to the method described above for preparing the charge transport layer. Figure 2 When the positive light-emitting diode shown contains a hole injection layer, the hole injection layer is used as the substrate 1. On the outer surface of the hole injection layer, a hole transport material ink is used as the second solution, and a hole transport layer 20 is prepared according to the method for preparing the charge transport layer described above. Then, a light-emitting layer 30, an electron transport layer 40 (or a hole injection layer is further formed), and a cathode 50 are sequentially formed on the outer surface of the hole transport layer 20 according to existing methods.
[0055] When the electron transport layer 40 is prepared by the above method for preparing the charge transport layer, the light-emitting layer 30 is used as the substrate 1, and electron transport material ink is used as the second solution on the outer surface of the light-emitting layer 30, and the electron transport layer 40 is prepared according to the above method for preparing the charge transport layer.
[0056] In another embodiment, the structure of the inversion-type light-emitting diode is as follows: Figure 3 As shown, it includes a stacked structure of an anode 10 and a cathode 50 disposed opposite to each other. The cathode 50 can be stacked and bonded on a substrate 01. A light-emitting functional layer is stacked and bonded between the anode 10 and the cathode 50. The light-emitting functional layer includes a light-emitting layer 30, a hole transport layer 20, and an electron transport layer 40. From the anode 10 to the cathode 50, the hole transport layer 20, the light-emitting functional layer 30, and the electron transport layer 40 are stacked sequentially. Furthermore, a hole injection layer can also be disposed between the hole transport layer 20 and the anode 10. Figure 2 (Not shown), an electron injection layer can also be provided between the electron transport layer 40 and the cathode 50. Figure 2 (Not displayed).
[0057] When the electron transport layer 40 is prepared using the method described above for preparing the charge transport layer, the cathode 50 is used as the substrate 1, and electron transport material ink is used as the second solution on the outer surface of the cathode 50, and the electron transport layer 40 is prepared according to the method described above for preparing the charge transport layer. Figure 2 When the inverting light-emitting diode shown contains an electron injection layer, the electron injection layer is used as the substrate 1. On the outer surface of the electron injection layer, an electron transport material ink is used as the second solution, and an electron transport layer 40 is prepared according to the method for preparing the charge transport layer described above. Then, according to existing methods, a light-emitting layer 30, a hole transport layer 20 (or a hole injection layer is further formed), and an anode 10 are sequentially formed on the outer surface of the electron transport layer 40.
[0058] When the hole transport layer 20 is prepared by the above method for preparing the charge transport layer, the light-emitting layer 30 is used as the substrate 1, and hole transport material ink is used as the second solution on the outer surface of the light-emitting layer 30, and the hole transport layer 20 is prepared according to the above method for preparing the charge transport layer.
[0059] To enable those skilled in the art to clearly understand the above-described implementation details and operations of the present invention, and to demonstrate the significant advancements in the charge transport layer preparation method and the light-emitting diode and its preparation method of the present invention, the following examples illustrate the above technical solutions.
[0060] In the following embodiments, QLED is used as an example for description. The structure of the QLED is ITO / hole transport layer (30nm) / CdSe / ZnS (40nm) / electron transport layer (40nm) / Ag (120nm). It should be understood that this QLED structure is merely exemplary, and the present invention is not limited thereto.
[0061] Example 1
[0062] This embodiment provides a QLED light-emitting diode and its fabrication method.
[0063] The structure of the QLED light-emitting diode is as follows: Figure 2 The positive quantum dot light-emitting diode shown has the following structure: ITO / PEDOT:PSS (30nm) hole transport layer (30nm) / CdSe / ZnS (40nm) / electron transport layer (40nm) / Ag (120nm). The " / " indicates the layer connection relationship of the stacked structure.
[0064] The QLED fabrication method in this embodiment includes the following steps:
[0065] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0066] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0067] S3: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot luminescent layer to form a zinc oxide electron transport wet film layer, which is also the second film layer; then, a triethylamine-acetone solution is deposited on the surface of this zinc oxide electron transport wet film layer to form a triethylamine-containing first film layer, thereby forming a zinc oxide-triethylamine composite wet film layer. Then, it is heat-treated at 120°C for 50 minutes in an inert atmosphere to form a zinc oxide electron transport layer; wherein, in the zinc oxide-triethylamine composite wet film layer, the molar ratio of triethylamine to zinc oxide is 2:1;
[0068] S4: Deposit the top electrode on the zinc oxide electron transport layer.
[0069] Example 2
[0070] This embodiment provides a QLED light-emitting diode and its fabrication method.
[0071] The structure of the QLED light-emitting diode is as follows: Figure 2 The positive quantum dot light-emitting diode shown has the same structure as in Example 1.
[0072] The QLED fabrication method in this embodiment includes the following steps:
[0073] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0074] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0075] S3: First, a triethylamine-acetone solution is deposited on the surface of the quantum dot luminescent layer to form a first triethylamine film layer; then, a zinc oxide-ethanol solution is deposited on the surface of the first film layer to form a zinc oxide electron transport wet film layer, thereby forming a zinc oxide-triethylamine composite wet film layer. Then, it is heat-treated on a heating stage at 150°C for 30 minutes in an inert atmosphere to form a zinc oxide electron transport layer; wherein, in the zinc oxide-triethylamine composite wet film layer, the molar ratio of triethylamine to zinc oxide is 2:1;
[0076] S4: Deposit the top electrode on the zinc oxide electron transport layer.
[0077] Example 3
[0078] This embodiment provides a QLED light-emitting diode and its fabrication method.
[0079] The structure of the QLED light-emitting diode is as follows: Figure 2 The positive quantum dot light-emitting diode shown comprises an ITO / NiO hole transport layer (30nm) / CdSe / ZnS (40nm) / zinc oxide electron transport layer (40nm) / Ag (120nm). The " / " indicates the stacked layer structure connection.
[0080] The QLED fabrication method in this embodiment includes the following steps:
[0081] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0082] S2: Spin-coat a NiO-water solution onto the bottom electrode to form a NiO hole transport wet film layer; then deposit a triethylamine-n-butanol solution on the surface of the NiO hole transport wet film layer to form a triethylamine functional wet film layer, thereby forming a NiO-triethylamine composite wet film layer; then heat-treat on a heating stage at 120°C for 30 minutes to form a NiO hole transport layer.
[0083] S3: A quantum dot light-emitting layer is formed on the surface of the NiO hole transport layer;
[0084] S4: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot light-emitting layer to form a zinc oxide electron transport wet film layer; then, the zinc oxide electron transport wet film layer is directly heat-treated on a heating stage at 100°C for 50 mins in an inert atmosphere to form a zinc oxide electron transport layer.
[0085] S5: Deposit the top electrode on the zinc oxide electron transport layer.
[0086] Comparative Example 1
[0087] This comparative example provides a QLED light-emitting diode and its fabrication method. The structure of the QLED light-emitting diode in this comparative example is the same as that in Example 1. However, the zinc oxide electron transport layer in the QLED light-emitting diode differs from that in Example 1 and is fabricated according to step S3 of the following QLED light-emitting diode fabrication method.
[0088] The preparation method of this comparative QLED includes the following steps:
[0089] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0090] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0091] S3: Deposit a zinc oxide-ethanol solution on the quantum dot luminescent layer to form a zinc oxide electron transport wet film layer; then heat-treat the zinc oxide electron transport wet film layer directly on a heating stage at 120°C for 15 minutes to form an electron transport layer;
[0092] S4: Deposit the top electrode on the zinc oxide electron transport layer.
[0093] Comparative Example 2
[0094] This comparative example provides a QLED light-emitting diode and its fabrication method. The structure of the QLED light-emitting diode in this comparative example is the same as that in Example 1. However, the zinc oxide electron transport layer in the QLED light-emitting diode differs from that in Example 1 and is fabricated according to step S3 of the following QLED light-emitting diode fabrication method.
[0095] The preparation method of this comparative QLED includes the following steps:
[0096] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0097] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0098] S3: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot light-emitting layer to form a zinc oxide electron transport wet film layer; then, a n-butylamine-acetone solution is deposited on the surface of the electron transport wet film layer to form a n-butylamine first film layer, thereby forming a zinc oxide-n-butylamine composite wet film layer. Then, the zinc oxide electron transport layer is formed by heat treatment on a heating stage at 120°C for 50 minutes in an inert atmosphere.
[0099] Comparative Example 3
[0100] This comparative example provides a QLED light-emitting diode and its fabrication method.
[0101] The structure of the QLED light-emitting diode is as follows: Figure 2 The positive quantum dot light-emitting diode shown has the same structure as in Example 1. However, the zinc oxide electron transport layer in the QLED light-emitting diode differs from that in Examples 1 and 2, and is prepared according to step S3 of the following QLED light-emitting diode fabrication method.
[0102] The QLED fabrication method in this embodiment includes the following steps:
[0103] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0104] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0105] S3: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot luminescent layer to form a zinc oxide electron transport wet film layer; then, a tripropylphosphine-methyl formate solution is deposited on the surface of this electron transport wet film layer to form a tripropylphosphine first film layer, thereby forming a zinc oxide-tripropylphosphine composite wet film layer. Then, it is heat-treated on a heating stage at 100°C for 50 mins in an inert atmosphere to form a zinc oxide electron transport layer; wherein, in the zinc oxide-tripropylphosphine composite wet film layer, the mass ratio of tripropylphosphine to zinc oxide is 2:1.
[0106] S4: Deposit the top electrode on the zinc oxide electron transport layer.
[0107] Comparative Example 4
[0108] This comparative example provides a QLED light-emitting diode and its fabrication method. The structure of the QLED light-emitting diode in this comparative example is the same as that in Example 1. However, the zinc oxide electron transport layer in the QLED light-emitting diode differs from that in Example 1 and is fabricated according to step S3 of the following QLED light-emitting diode fabrication method.
[0109] The preparation method of this comparative QLED includes the following steps:
[0110] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0111] S2: An organic hole injection layer, an organic hole transport layer, and a quantum dot light-emitting layer are sequentially deposited on the bottom electrode;
[0112] S3: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot light-emitting layer to form a zinc oxide electron transport wet film layer; then, a tripropylamine-acetone solution is deposited on the surface of the electron transport wet film layer to form a tripropylamine first film layer, thereby forming a zinc oxide-tripropylamine composite wet film layer. Then, the zinc oxide electron transport layer is formed by heat treatment on a heating stage at 120°C for 50 minutes in a vacuum environment of -0.1MPa.
[0113] S4: Deposit the top electrode on the zinc oxide electron transport layer.
[0114] Comparative Example 5
[0115] This comparative example provides a QLED light-emitting diode and its fabrication method. The structure of the QLED light-emitting diode in this comparative example is the same as that in Example 3. However, the NiO hole transport layer in the QLED light-emitting diode differs from that in Example 3 and is fabricated according to step S2 of the following QLED light-emitting diode fabrication method.
[0116] The preparation method of this comparative QLED includes the following steps:
[0117] S1: Provide a substrate on which a bottom electrode (anode) is formed;
[0118] S2: Spin-coat NiO-water solution onto the bottom electrode to form a NiO hole transport wet film layer; then directly heat-treat the NiO hole transport wet film layer on a heating stage at 120°C for 30 minutes to form a NiO hole transport layer.
[0119] S3: A quantum dot light-emitting layer is formed on the surface of the NiO hole transport layer;
[0120] S4: First, a zinc oxide-ethanol solution is deposited on the surface of the quantum dot light-emitting layer to form a zinc oxide electron transport wet film layer; then, the zinc oxide electron transport wet film layer is directly heat-treated on a heating stage at 100°C for 50 mins in an inert atmosphere to form a zinc oxide electron transport layer.
[0121] S5: Deposit the top electrode on the zinc oxide electron transport layer.
[0122] Quantum dot light-emitting diode photoelectric performance testing
[0123] The QLED devices prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested at 50 mA·cm⁻¹. -2 The EQE results at current density are shown in Table 1. It can be seen from the table that the EQE of the device after triethylamine treatment is improved, indicating that triethylamine optimizes the thin film state of the electron transport layer.
[0124] Table 1
[0125]
[0126] Furthermore, the QLED devices prepared in Example 1, Example 2, and Comparative Example 3 were tested at 50 mA·cm⁻¹. -2 The EL topography at current density is shown in the following figures. Figure 4 As shown.
[0127] Based on the EQE data in Table 1, comparing the EQE of the QLEDs provided in Examples 1 and 2 with the EQE of the QLED device provided in Comparative Example 1, the EQE values of Examples 1 and 2 are significantly higher than the EQE value of Comparative Example 1.
[0128] Comparing the EQE of the QLED provided in Example 3 with the EQE of the QLED device provided in Comparative Example 5, the EQE value of Example 3 is also significantly higher than the EQE value of Comparative Example 5.
[0129] This indicates that using triethylamine as a functional material can effectively bind to the dangling bonds of metal cations on the surface of metal oxide nanocrystals, achieving a capping effect. During the ink solvent evaporation process, the metal oxide nanocrystals first form a stable state similar to "oligomers." During the deposition process of the metal oxide nanocrystals, these "oligomers" undergo an ordered arrangement similar to polymer polymerization, making the deposition process more ordered, reducing the chance of defects in the film formation process, and the triethylamine is easily removed when the solvent evaporation ends. Furthermore, the combination... Figure 4 (a) and Figure 4 (b) It can be seen that the electron transport layer film formed by triethylamine as a functional material has not only small defects but is also uniform, which makes the EQE of QLED in Example 1 and Example 2 higher than that in Comparative Example 1, and the EQE of QLED in Example 3 higher than that in Comparative Example 5.
[0130] Comparing the EQE of the QLEDs provided in Examples 1 and 2 with the EQE of the QLED device provided in Comparative Example 3, the EQE values of Examples 1 and 2 are significantly higher than the EQE value of Comparative Example 3.
[0131] Combination Figure 4 and compare Figure 4 (a) Figure 4 (b) and Figure 4 (c) The reason for this may be that the bond energy between phosphine compounds and metal oxide nanocrystals is relatively strong, making it difficult to remove in subsequent processes. This affects the film-forming properties of the zinc oxide-tripropylphosphine composite wet film, resulting in an uneven zinc oxide electron transport layer. Figure 4 The EL morphology shown in (c) affects the luminous efficiency of the QLED and reduces the EQE value of the QLED.
[0132] Comparing the EQE of the QLEDs provided in Examples 1 and 2 with those in Comparative Examples 2 and 4, the EQE values of Examples 1 and 2 are significantly higher than those of Comparative Examples 2 and 4. This indicates that n-butylamine and tripropylamine, as functional materials, cannot achieve the ordered arrangement of metal oxide nanocrystals in the electron transport layer to reduce defects in the electron transport layer. The reason for this may be that although n-butylamine, like triethylamine, has electron-donating groups, its steric hindrance effect is weak and cannot prevent the agglomeration of the capped metal oxide nanocrystals. In other words, the metal oxide nanocrystal material agglomerated in the electron transport layer of Comparative Example 2, thus failing to achieve an ordered arrangement. Therefore, the EQE of the QLED in Comparative Example 2 is close to that of Comparative Example 1. In Comparative Example 4, tripropylamine, as a functional material, also failed to achieve the expected results. It is speculated that this may be because tripropylamine has a weak binding ability with metal oxides, making it difficult for it to reach the stable state of "oligomers" and thus unable to "guide" it to complete the orderly arrangement. Therefore, the EQE of the QLED in Comparative Example 3 is also close to that in Comparative Example 1.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for fabricating a charge transport layer, characterized in that: Includes the following steps: A first film layer is formed using a first solution containing a functional material, and a second film layer is formed using a second solution containing a charge transport material, wherein the first film layer and the second film layer are in contact with each other, or a mixed film layer is formed using a mixed solution of the first solution and the second solution; In an inert gas atmosphere, the first film layer and the second film layer, or the mixed film layer, are heat-treated at 90°C to 150°C to volatilize the functional materials and solvents, thereby obtaining the charge transport layer. The functional material is an organic compound containing electron-donating groups, and the surface of the charge transport material has metal cation dangling bonds, wherein the electron-donating groups can bind to the metal cation dangling bonds.
2. The preparation method according to claim 1, characterized in that: The functional material includes triethylamine.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the functional material to the charge transport material is 1.5 to 3:
1.
4. The preparation method according to any one of claims 1-3, characterized in that: In the first solution, the volume ratio of the functional material to the solvent is 1:(1~50); and / or The solvent of the first solution includes at least one of acetone, n-butanol, tetrahydrofuran, and methyl formate.
5. The preparation method according to any one of claims 1-3, characterized in that: The charge transport material is a hole transport material or an electron transport material.
6. The preparation method according to claim 5, characterized in that: The hole transport material includes at least one of MoO3, NiO, V2O5 and WO3, or includes at least one of MoO3, NiO, V2O5 and WO3 doped with at least one metal of Li, Al, Mg, Cs, In, Ga and Zr.
7. The preparation method according to claim 5, characterized in that: The electron transport material includes at least one of ZnO, SnO, TiO2 and ZrO2, or includes at least one of ZnO, SnO, TiO2 and ZrO2 doped with at least one of Li, Al, Mg, Cs, In, Ga and Zr.
8. A light-emitting diode, characterized in that: It includes an electron transport layer and / or a hole transport layer, wherein the electron transport layer is prepared according to the preparation method according to any one of claims 1-4, and the charge transport material is an electron transport material. The hole transport layer is prepared according to the preparation method of any one of claims 1-4, and the charge transport material is a hole transport material.
9. The light-emitting diode according to claim 8, characterized in that: The light-emitting diode is either QLED or OLED.
Citation Information
Patent Citations
Quantum dots made using phosphine
CN105378027A
Preparation method for amino nano-TiO2 / SiO2 compound fiber membrane, product and application thereof
CN107626287A